2016
DOI: 10.1097/sap.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Breast Reconstruction in Women Older Than 65 Years Versus Women Younger Than 65 Years

Abstract: This is the largest study to compare patients undergoing autologous breast reconstruction older than and younger than 65 years within the same cohort. Women older than 65 years represent a minority and constituted only 3% of patients in this multicenter 10-year review. We have shown that with careful patient selection, abdominally based autologous reconstruction should be considered in the elderly patient population because it is well tolerated and achieves high patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 38 publications
4
43
1
1
Order By: Relevance
“…Our results confirm previous findings that advancing age is not a predictor of complications following breast reconstruction (15, 17, 30). However, we did observe significant age-related differences in some of the PRO measures; while older women reported greater sexual well-being than younger women, patients over 60 years were less satisfied with their reconstruction than their younger counterparts.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results confirm previous findings that advancing age is not a predictor of complications following breast reconstruction (15, 17, 30). However, we did observe significant age-related differences in some of the PRO measures; while older women reported greater sexual well-being than younger women, patients over 60 years were less satisfied with their reconstruction than their younger counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…Results from studies evaluating PROs in older women undergoing breast reconstruction are more consistent in their findings, demonstrating that older women achieve similar or even higher levels of satisfaction than younger women post-reconstruction (14, 15, 28, 29). For example, Sisco and coworkers (29) conducted a prospective cohort study of 315 patients undergoing immediate reconstruction and found that patients over 65 years of age achieved similar quality of life scores to younger patients.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Previous studies of age effects on breast reconstruction complications have produced mixed results. A multicenter, retrospective analysis by Song et al 17 assessing outcomes of autologous reconstructions in 1809 patients concluded that complications in elderly patients were “equivalent,” compared with those of younger women. In an analysis of free flap breast reconstructions, Selber et al 18 reported no difference in complications between patients under 65 and those 65 years or older.…”
Section: Discussionmentioning
confidence: 99%